KAJIAN KONFIGURASI PESAWAT TEMPUR GENERASI 4 DAN GENERASI 5 - Suwarni, Ika (Sekolah Tinggi Teknologi Adisutjipto, 2016)
The important aircraft combat role for air defense, based on the state to develop a fighter with capabilities increasingly sophisticated. Until 2016, the fighter who is still being developed fighter 4th generation and 5th generation. Basically, the classification generation combat aircraft does not have a basic standard. In this study, will be evaluating of fighter technology in the world of the configuration aspect. Based on the configuration and design goals, there were marked differences between the 4th and 5th generation. Studies in the literature data come only in the form of printed and electronic articles are public domain data. Part studied in pattern 4th and 5th generation are nose, wing, fuselage, tail, engine and weapon configurations. The fifth generation fighter concept is low Radar Cross Section, so that the aircraft is difficult to identify the other. This concept is in the design of the internal weapon bay, blended wing body, internal fuel tank, low observable inlet, and the use of radar absorbent material in the composite. Each aircraft that does not have these characteristics, it is included in the fourth generation. The results of the study can be used as reference for the development of 4th or 5th generation fighter.